Association between Biofilm Formation and Virulence Genes Expression and Antibiotic Resistance Pattern in Proteus mirabilis, Isolated from Patients of Dhaka Medical College Hospital - Mishu, Nafisa Jabin; SM, Shamsuzzaman; HM, Khaleduzzaman; Nabonee, Modina Ansary; dola, Nigha zannat; haque, Azmeri (Archives of Clinical and Biomedical Research, 2022)
Multidrug resistance (MDR) and extensive drug resistance (XDR) Proteus mirabilis are great threat to public health. Along with the drug resistance the biofilm forming capacity of these bacteria further complicate the treatment of infections caused by it. Furthermore, emergence of multidrug resistant Proteus mirabilis is increasing day by day. This study analyzed the relationship between antibiotic resistance and biofilm formation among the isolated Proteus mirabilis. It was a cross-sectional study over a period of one year from July 2019 to June 2020 at Dhaka Medical College Hospital. In this study we found that biofilm producing Proteus mirabilis were more antibiotic resistant than non-biofilm producing Proteus mirabilis. The biofilm formation was significantly higher in extended spectrum beta lactamase (ESBL) producing strains than non- extended spectrum beta lactamase (ESBL) producing strains but no significant relationship was observed between biofilm formation with MDR and XDR Proteus mirabilis. Indeed multidrug-resistant isolates did not show a trend to being greater biofilm producers than non-multidrug resistant isolates.